Raising the cub - distributed realtime support in Tigger - CAHILL, VINNY (German UNIX User Group, 1994)
We present a proposal for an architecture supporting distributed objects exhibiting soft real-time behaviour. This support is aimed directly at the eld of distributed multimedia applications. Since the architecture is designed in a modular fashion, we expect that this architecture can be easily extended to other application areas with similar demands such as distributed video games, a major future market. The design consists of a metalevel approach with four individual levels oering a clean separation between baselevel objects implementing application functionality, on one side and metalevel objects, responsible for control of behaviour of baselevel objects, on the other side.
Proceedings of the German UNIX User Group
German UNIX User Group
PUBLISHED
Keywords: Computer Science